2021
DOI: 10.3390/foods10061400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tetrapeptide-FSEY on Oxidative and Physical Stability of Hazelnut Oil-In-Water Emulsion

Abstract: This study investigates the antioxidant behaviors of a hazelnut tetrapeptide, FSEY (Phe-Ser-Glu-Tyr), in an oil-in-water emulsion. The emulsion was prepared with stripped hazelnut oil at a ratio of 10%. O/W emulsions, both with and without antioxidants (FSEY and TBHQ), were incubated at 37 °C. The chemical stabilities, including those of free radicals and primary and secondary oxidation productions, along with the physical stabilities, which include particle size, zeta-potential, color, pH, and ΔBS, were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The oil-in-water emulsion was prepared according to a previous study. To obtain oil without any antioxidants, hazelnut crude oil was stripped by silica gel, activated charcoal, and sucrose [ 28 ]. The aqueous phase of the emulsion was prepared by dispersing 0.5 wt% Tween 20 in 10 mM phosphate buffer at pH 7.0 followed by stirring at room temperature for 20 min to ensure complete dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…The oil-in-water emulsion was prepared according to a previous study. To obtain oil without any antioxidants, hazelnut crude oil was stripped by silica gel, activated charcoal, and sucrose [ 28 ]. The aqueous phase of the emulsion was prepared by dispersing 0.5 wt% Tween 20 in 10 mM phosphate buffer at pH 7.0 followed by stirring at room temperature for 20 min to ensure complete dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…Formation Kinetics of Lipid Hydroperoxides. The kinetic analysis of lipid hydroperoxide content in emulsion was performed using a modification of the method published by Shi et al 24 0.2 mL of emulsion was added to 1.5 mL of solution of isooctane and 2-propanol (3:1 v/v) to extract hydroperoxides formed during oxidation of lipid. The mixed solution was vortexed three times for 10 s each time.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Changes in the chemical structure of foods as a result of heat treatments such as roasting, heating, boiling and during storage are accompanied by variations in their colors. For this reason, many researchers have examined the color change of hazelnut oil under different extraction, refining and storage conditions (Shi et al, 2021). For example, Karabulut et al (2005) reported that the L* (brightness) value of crude oil increased compared to refined oil, while the values of a* (redness) and b* (yellowness) decreased.…”
Section: Introductionmentioning
confidence: 99%